(untitled) (Advancements in Homeopathic Research, 2024)
Background: Fish is the earliest, most prolific, and most diversified class of vertebrates with around 34,000 species. Various species of fish have been used as research models all around the world to provide insights into intricate human genetics, anatomical and physiological systems, and the pathophysiology of human illnesses. Aim: This study aimed to highlight experimental studies of fish models in Homoeopathy using a variety of evaluation parameters along with validated analytical tools for traceable evidence. Methods: The information was gathered for preclinical research studying the impact of Homoeopathic formulations on disorders in a variety of fish, from a number of databases such as Scopus, Science Direct, Web of Science, PubMed, Research Gate, and Google Scholar. Result: There were 30 publications in all that were evaluated, and of them, 25 met the inclusion criteria and were included in the scoping review. Conclusion: The use of fish models in Homoeopathic research can be considered to be valuable as it gives a versatile approach that can significantly contribute to our understanding of biology, disease, and environmental science. Subsequently, the fish models enhance the ability of researchers to make advanced discoveries in various fields of study.